DETERMINASI DISIPLIN, PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. WILLINTON CIPTA PRIMA BATAM - Novia Orientiani; Jemmy Rumengan (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2017)
The purpose of this research was for testing and analyzing determinant of disciplination, training and compensation of employee performance in PT. Willinton Cipta Prima Batam. Disciplination and training are such an important rule in performance value, and compensation has influence to employee performance, when higher compensation the employee could get, would be higher the performance they would give. Performance is comparation of output the employee could reached of the company’s standart. Testing data technique that used in this research includes validation test with factor analyze, reliability test with Cronbach Alpha. Classic asumtion test and multiple linear regression analyze for testing and proofing the hyphotesis of this research. Collecting data was using questionnaire, and analyzed by software SPSS version 21.The result of hyphotesis test for discliplination, has positive influence to employee performance, with t test was 2.700, in significance by 0,010, means hyphotesis of this research was accepting Ha and rejecting Ho. Second hyphotesis of training showed, it has influence to employee performance by 10.857 with significance level by 0.000 which means accepting Ho and rejecting Ha. Third hyphotesis showed that compensation has influence to employee performance